The Principle of Independence in the Fulfillment of Tax Obligations in the Context of Digitalization of the Economy - O. I. Lyutova (Теоретическая и прикладная юриспруденция)
The study considers the conceptual problem of transforming the content of one of the principles of the institution of tax liability — the independence of its execution — in the context of its development in the information environment and in the conditions of the active use of modern digital technologies in the implementation of tax relations.It is proved that in the modern realities of the digital transformation of taxation in the field of legal regulation of the principle of independence of the fulfillment of the tax obligation, two interrelated trends are realized: firstly, the delegation of the obligation to calculate taxes to the tax authority not only in relation to individuals, but also for organizations and individual entrepreneurs; secondly, there is an expansion of the list of powers of tax authorities related to the fulfillment of the obligation to pay tax.The author analyzes various novelties of the tax legislation of the Russian Federation from the point of view of the use by the legislator of the principle of independence in regulating the tax legal relations of the digital era. In conclusion, it was concluded that digitalization leads to a gradual reduction in the number of taxpayers’ tax obligations, which is implemented primarily by imposing them on both the tax authorities and other participants in tax legal relations.